Facies analysis, stratigraphic architecture and depositional environments of the Guanajuato conglomerate in the Sierra de Guanajuato, Mexico - María Jesús Puy-Alquiza (Boletín de la Sociedad Geológica Mexicana, 2017)
The fluvial stratigraphic architecture of the Cenozoic Guanajuato Conglomerate in the Sierra de Guana- juato records part of the infill of continental exten - sional basins formed after the Laramide Orogeny in the Mesa Central, Mexico. Coarse-grained strata of the Guanajuato Conglomerate represent the deposit of a major channel belt (1 to 2 km wide by >100 km long). This channel belt deposits comprises a 2000 m-thick conglomeratic interval interbedded with deposits of matrix-supported gravel, sandstones and mudstones. Facies analysis indicates that Guanajua - to Conglomerate were deposited in alluvial fans and fluvial environments. Facies of the Guanajuato Con - glomerate include sandy matrix conglomerate (that shows evidence of traction-dominated deposition), debris-flow (Gms) and hyperconcentrated-flow depos- its (Sgpc) (interpreted as turbulent gravity flows), and sandstones with plane to horizontal stratification and planar and through cross-stratification, ripples, rain mark, flutes, groove marks, and massive mudstones, mudstones with fine lamination and with desiccation cracks. Based on established facies associations, five architectural elements and 14 facies were determined from nine locations as a result of Eocene post-Lar - amide sedimentation in the southern Mesa Central. The Guanajuato Conglomerate was divided in two members: Lower and Upper members. The Lower Member unconformably overlies a Mesozoic assem - blage (intrusive complex and eruptive sequence as- semblage and Guanajuato arc assemblage) and has a thickness between 700 and 1300 m. The Lower Member is composed of two parts: 1) The basal portion includes conglomerate layers interbedded with sandstones and lava flows. The upper part of the Lower Member conglomerate is caused by de- bris-flow and hyperconcentrated-flow, major tabular and lenticular sandstone, and siltstone. The Upper Member is characterized by clast-supported conglom- erate interbedded with sandstone-mudstone beds. The crudely stratified, imbrications, pebble clusters, coarse to pebbly sandstone, indicate channel lag de- posits within a heavy loaded fluvial system. The fine- grained sandstone, rain mark, parallel lamination, desiccation cracks, may be interpreted as side bar sediments deposited by shift channels during lower flow conditions. Sediment distribution patterns and stratigraphic architecture, suggest that the deposition- al system is a braided fluvial for the Lower Member, while the Upper Member corresponds to alluvial fan environment.